Cigarette smoking and serum lipid and lipoprotein concentrations: an analysis of published data. Issue 6676 (25th March 1989) - Craig, W. Y.; Palomaki, G. E.; Haddow, J. E.
Abstract : To examine the association between cigarette smoking in adults and serum lipid and lipoprotein concentrations the results of 54 published studies were analysed. Overall, smokers had significantly higher serum concentrations of cholesterol (3.0%), triglycerides (9.1%), very low density lipoprotein cholesterol (10.4%), and low density lipoprotein cholesterol (1.7%) and lower serum concentrations of high density lipoprotein cholesterol (-5.7%) and apolipoprotein AI (-4.2%) compared with nonsmokers. Among non-smokers and light, moderate, and heavy smokers a significant dose response effect was present for cholesterol (0, 1.8, 4.3, and 4.5% respectively), triglycerides (0, 10.7, 11.5, and 18.0%), very low density lipoprotein cholesterol (0, 7.2, 44.4, and 39.0%), low density lipoprotein cholesterol (0, -1.1, 1.4, and 11.0%), high density lipoprotein cholesterol (0, -4.6, -6.3, and -8.9%), and apolipoprotein AI (0, -3.7 and -5.7% in non-smokers and light and heavy smokers). These dose response effects may provide new evidence for a causal relation between exposure to cigarette smoke and changes in serum lipid and lipoprotein concentrations whether as a direct result of physiological changes or of dietary changes induced by smoking. Adequate prospective data to estimate the excess risk of coronary artery disease existed only for cholesterol concentration. When that information was combined with data from the present study, and given that smokers as a group face an average overall excess risk of coronary artery disease of 70%, it was estimated that the observed increased serum cholesterol concentration in smokers may account for at least 9% of that excess risk. Furthermore, the dose response effect of smoking on serum cholesterol concentration suggests a gradient of increased absolute risk of coronary artery disease between light and heavy smokers.